Physical activity and sleep quality among Chinese college students: the serial mediating roles of anxiety and depression - Zhang, Zhiwei; Liu, Zhaozhi; Lin, Yongxia; Guo, Mingkun; Xu, Xiongzhuang; Peng, Li (Frontiers in Psychology, 2025)
ObjectivePhysical activity is a modifiable lifestyle factor that plays a significant role in promoting mental health and sleep quality. However, empirical studies exploring the mechanisms by which varying intensities of physical activity influence sleep quality—particularly the mediating roles of anxiety and depression—remain limited. This study aims to investigate the relationships between moderate- and vigorous-intensity physical activity and sleep quality among Chinese university students, with a focus on the serial mediating effects of anxiety and depression.MethodsA cross-sectional survey was conducted from October to November 2024, employing convenience sampling to recruit 5,803 undergraduate students from a university in Chongqing, China. Participants completed the International Physical Activity Questionnaire-Short Form (IPAQ-SF), the Pittsburgh Sleep Quality Index (PSQI), the Generalized Anxiety Disorder 7-item scale (GAD-7), and the Patient Health Questionnaire-9 (PHQ-9). Data were analyzed using a bootstrap-based serial mediation model.Results(1) Compared to the low-intensity physical activity group, students engaging in moderate- and vigorous-intensity physical activity exhibited significantly lower levels of anxiety (F = 380.82, p < 0.01) and depression (F = 410.56, p < 0.01), along with better sleep quality (F = 594.25, p < 0.01). (2) Physical activity intensity was negatively correlated with sleep quality (r = −0.374, p < 0.01), anxiety (r = −0.299, p < 0.01), and depression (r = −0.306, p < 0.01); sleep quality was positively correlated with anxiety (r = 0.455, p < 0.01) and depression (r = 0.471, p < 0.01); anxiety and depression were highly positively correlated (r = 0.840, p < 0.01). (3) Serial mediation analysis indicated that moderate- and vigorous-intensity physical activity not only had direct effects on sleep quality but also exerted indirect effects through the independent and serial mediating roles of anxiety and depression.ConclusionAmong Chinese university students, different intensities of physical activity are significantly associated with anxiety, depressive symptoms, and sleep quality. Moderate- and vigorous-intensity physical activity levels are significantly correlated with lower anxiety and depression scores and better sleep quality. Serial mediation analysis further reveals that anxiety and depression have significant indirect effects in the relationship between physical activity intensity and sleep quality, indicating that the association between physical activity and sleep quality is partially influenced by the serial effects of anxiety and depression. Notably, vigorous-intensity physical activity demonstrates a stronger association with these psychological indicators and sleep quality.